EVALUATION OF SUSTAINABLE TRADITIONAL BUILDINGS IN THE CONTEXT OF ENERGY EFFICIENCY AND CONSERVATION - Özalp, Nihal Arda (International Journal of Research -GRANTHAALAYAH, 2020)
The new world order started by the industrial revolution; have initiated significant changes on the cities, as well as the lifestyle in which societies, their technologies, their understanding of the use of the natural environment and the way in which they exploit natural energy resources. The effects of industrialization on the environment, energy resource consumption and spatial conditions by transforming consumption habits as well as production types; caused important problems in the twentieth century especially in urban residential areas. The building sector, which consumes two fifths of the world resources; has been recognized worldwide that it is consuming limited resources with its energy preferences and consumption profiles along with environmental and climatic damage. For this reason, searches for solutions, different spatial planning approaches and scientific studies have started to meet the reality that limited resources are running out. Along with sustainability studies, which is one of these approaches, the sensitivity of the building planning principles of traditional residential areas that have reached from past to present has begun to draw attention to energy efficient usage decisions. The aim of the study is to evaluate design parameters related to energy efficiency and natural resource use of the design approaches of structures in traditional residential areas with the potential to be solutions to problems. Within the scope of the study, the design parameters related to energy conservation and efficiency of sustainable traditional buildings, which are revealed with different climatic and environmental data in traditional residential areas of Anatolia, are discussed together with the literature researches and on-site evaluations. The study aims to reveal the sustainable traditional architectural principles that these buildings have in energy efficiency, use and conservation in the context of examples examined in different climatic regions.